REAKSI PASAR MODAL ATAS KEBIJAKAN INVESTASI DAN KEBIJAKAN PENDANAAN PADA PERUSAHAAN BERTUMBUH DAN TIDAK BERTUMBUH - Satriya, I Wayan Budi (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME 03.NO.08.TAHUN 2014, 2014)
This research target is to obtain empirical evidence of difference influence information capital expenditure and debt equity ratio (DER) changes related to cumulative abnormal return on growing and non growing companies. Population in this research is the companies which are listed at the Indonesian Stock Exchange year 2007-2011. Sample selection use the technique of purposive sampling. Data were analyzed using  regression analysis. Result of research show the capital expenditure have  positifely influence to the cumulative abnormal return on growing companies, on the other hand capital expenditure does not influence to cumulative abnormal return on non growing companies. Debt equity ratio changes does not influence to cumulative abnormal return on non growing and growing companies.
Keywords: pengeluaran modal, debt to equity ratio, cumulative abnormal return